Evaluation of the reality of the application of electronic management in the General Sports Federation in Syria - رسلان علي; سراج ديوب (Latakia University Journal -Medical Sciences Series, 2023)
In light of the increasing progress in the use of modern technology and computer applications, the role of using electronic management has become an indispensable requirement and necessity in sports organizations, because of its positive results, such as improving service, efficiency and performance. The aim of the research is to identify the reality of the application of electronic management in the General Sports Federation. The researcher used the descriptive approach and the research sample consisted of (140) people from the human resources of the Sports Federation. To this end, he used a four-axis questionnaire: the computer hardware axis, the software axis, the networking axis, and the knowledge makers axis. The results of the research indicated that the reality of the application of electronic management in the organization of the General Sports Federation was moderate with a clear absence of electronic work. The researcher presented a number of recommendations, most notably attempts to modernize and develop the infrastructure with the latest equipment and technological means through the optimal use of government directives responsible for creating an enabling environment that promotes digital transformation. In the public sector, as well as raising the culture of electronic knowledge among the existing human resources by providing training courses and developing information and communication technology.